Reduced toxicity matched sibling bone marrow transplant results in excellent outcomes for severe congenital neutropenia - Oved, Joseph H.; Gibson, Nora M.; Venella, Kimberly; Elgarten, Caitlin W.; Wray, Lisa; Warren, Julia T.; Olson, Timothy S. (Frontiers in Immunology, 2024)
Severe congenital neutropenia (SCN) is caused by germline mutations, most commonly in ELANE, impacting neutrophil maturation and leading to high risk of life-threatening infections. Most patients with ELANE-mutant SCN can achieve safe neutrophil counts with chronic Granulocyte-Colony Stimulating Factor (G-CSF). However, up to 10% of patients have neutropenia refractory to G-CSF and require allogeneic stem cell transplant. Traditional conditioning for these patients includes busulfan and cyclophosphamide which is associated with significant toxicities. We present five patients with SCN without myeloid malignancy transplanted using a reduced toxicity regimen of busulfan, fludarabine and thymoglobulin. 5 pediatric patients with SCN underwent matched sibling donor bone marrow transplant (MSD-BMT) between 2014-2022 on or per CHP14BT057 (NCT02928991), a prospective, single center trial testing elimination of cyclophosphamide from conditioning in pediatric patients with single lineage inherited BMF syndromes. All patients had MSDs and no evidence of MDS. Conditioning consisted of PK-adjusted busulfan, fludarabine, and thymoglobulin, with calcineurin inhibitor and mycophenolate mofetil GVHD prophylaxis.With median follow-up of 48.4 months, overall and event-free survival were 100%. There was no acute GVHD and one instance of chronic limited GVHD. Patients exhibited >95% donor myeloid chimerism at 5 years post-BMT. Two patients experienced CMV reactivation without end-organ disease, and no other viral reactivation or significant infections occurred. MSD-BMT with reduced toxicity myeloablation for SCN provides excellent outcomes while minimizing toxicity. These data suggest that busulfan, fludarabine, and ATG can be considered an efficacious, low-toxicity standard of care regimen for patients with SCN undergoing MSD-BMT.